2021
DOI: 10.3389/fcvm.2021.782596
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Ajmaline and Thus Brugada Syndrome: Not Only the Sodium Channel!

Abstract: Ajmaline is an anti-arrhythmic drug that is used to unmask the type-1 Brugada syndrome (BrS) electrocardiogram pattern to diagnose the syndrome. Thus, the disease is defined at its core as a particular response to this or other drugs. Ajmaline is usually described as a sodium-channel blocker, and most research into the mechanism of BrS has centered around this idea that the sodium channel is somehow impaired in BrS, and thus the genetics research has placed much emphasis on sodium channel gene mutations, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Some practitioners prefer using ajmaline due to its higher sensitivity, which appears to result in a lower false-negative rate. Nevertheless, cautionary reports highlighted ajmaline's potential for false positives, emphasizing that a positive ajmaline test does not always confirm the presence of BrS in a patient [118]. Numerous studies emphasized the intricate mechanism of ajmaline, indicating that it does not function solely as a sodium channel blocker.…”
Section: Depolarization Disorder Repolarization Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Some practitioners prefer using ajmaline due to its higher sensitivity, which appears to result in a lower false-negative rate. Nevertheless, cautionary reports highlighted ajmaline's potential for false positives, emphasizing that a positive ajmaline test does not always confirm the presence of BrS in a patient [118]. Numerous studies emphasized the intricate mechanism of ajmaline, indicating that it does not function solely as a sodium channel blocker.…”
Section: Depolarization Disorder Repolarization Disordermentioning
confidence: 99%
“…associated with Brugada syndrome[6,108,[118][119][120][121].GeneProtein SCN5A Sodium channel protein type 5 subunit α SCN10A Sodium channel protein type 10 subunit α SCN1B Sodium channel subunit β-1 SCN2B Sodium channel subunit β-2 SCN3B Sodium channel subunit β-3 KCND2 Potassium voltage-gated channel subfamily D member 2…”
mentioning
confidence: 99%
“…AI and ML have helped characterize different types of heart failure with preserved ejection fraction [32] , AI-enabled ECG-based screening tool for the diagnosis of left ventricular systolic dysfunction [33] , and prediction of atrial fibrillation [34] . ECG-based ML algorithms are being used for the diagnosis of other inherited arrhythmias, such as long QT syndrome (LQTS) [35] . They found that among eight studies, the pooled SAUROC was 0.95 (95%CI: 0.31-1.00), sensitivity was 0.87 (95%CI: 0.83-0.90), and specificity was 0.91 (95%CI: 0.88-0.93), indicating good diagnostic performance.…”
Section: Ai In the Diagnosis Of Other Cardiac Diseasesmentioning
confidence: 99%
“…The plant Catharanthus roseus (Apocynaceae) is a medicinal plant that produces over 100 specialized metabolites classified as monoterpene indole alkaloids (MIAs). MIAs have diverse biological activities, including anti-cancer (vinblastine and vincristine), anti-psychotic (alstonine), anti-hypertensive (ajmaline) and anti-malarial (quinine) (van Der Heijden et al, 2004;Elisabetsky and Costa-Campos, 2006;Achan et al, 2011;Monasky et al, 2021). The universal MIA precursor in plants is strictosidine, a biosynthetic intermediate that is formed via an enzyme-catalyzed (strictosidine synthase, CrSTR) Pictet-Spengler condensation of the monoterpenoid secologanin and amino acid derived tryptamine (Figure 1A; Mizukami et al, 1979;Treimer and Zenk, 1979).…”
Section: Introductionmentioning
confidence: 99%